Unleashing cell-penetrating peptide applications for immunotherapy. Issue 6 (June 2022) - Koo, Ja-Hyun; Kim, Gil-Ran; Nam, Kyung-Ho; Choi, Je-Min
Abstract : With the advent of cancer immunotherapy, immunomodulation has emerged as an important strategy for the treatment of various diseases. We review recent advances in clinical trials of cell-penetrating peptide (CPP) applications for immunotherapy and also discuss their challenges and opportunities for preclinical studies in various immune diseases. CPP conjugation to antigenic peptides or proteins can enable efficient antigen uptake and cross-presentation by antigen-presenting cells (APCs), which induce both humoral and cytotoxic responses. In addition, CPP-coupled immune modulators can enhance antitumor immunity or anti-inflammatory effects to regulate allergies and autoimmunity. Given their huge advantages in overcoming delivery barriers, CPP-based strategies for immunomodulation could extend drug optimization and advance immunotherapy in various human diseases. Highlights: CPP conjugates can penetrate tissue barriers such as the blood–brain barrier and skin, that are difficult for other drugs to pass. CPP-conjugated antigen delivery in APCs or directly in vivo can increase the cytotoxic T lymphocyte (CTL) response as well as the antibody response by cross-presentation. CPP-conjugated cell fate controlling peptides or proteins can modulate lymphocyte function such as increasing regulatory T cell differentiation or inhibiting type 17 T helper cells to regulate autoimmunity, allergy, or organ transplantation. CPP-mediated molecular delivery for enhancing the type 1 T helper cell or CTL responses results in antitumor immunity and can enhance the efficacy of immune checkpoint inhibitors. There have been recent significant advances in clinical trials addressing human diseases using CPPs, such as CPP-coupled botulinum toxin A for cervical dystonia, TAT–PSD-95 for ischemic stroke, and TAT–JNKI-1 for hearing loss.